Design of attitude determination and control system for KIWISAT amateur satellite : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Engineering, Mechatronics, at Massey University, Albany, Auckland, New Zealand - Makarov, Kirill (Massey University, 2015)
This thesis is to present the design of “ADAC” system for “KiwiSat” cube satellite. An array of sensors were used: CMOS low resolution camera, sun sensor, earth horizon sensors, 3 axis magnetometer. The control of satellite rely on magnetic coils installed orthogonally to each other. Implementation of this system is essential to achieve the full control of the satellite when it reaches the lower orbit. Solution for the pitfall such as: the lack of torque of the satellite when it’s parallel to the earth magnetic field, was also designed. Attitude estimation is nonlinear due of kinematics and the reading of above sensors. Both a proportional-derivative controller and a linear quadratic regulator are implemented for control model of the system. And the Floquet Theory is used to check the stability of the controls, and an optimization method further optimizes the results. Model was constructed by simulink program that was packaged with mathematical software called “Matlab”. 3D model of the satellite was drawn in SolidWorks for the purpose of visual interaction and behavior.
Keywords: Artificial satellites; Attitude control systems; Attitude determination and control system (ADAC); KiwiSat; Sensors; Research Subject Categories::TECHNOLOGY::Other technology::Space engineering